2019
DOI: 10.1111/nyas.14087
|View full text |Cite
|
Sign up to set email alerts
|

The actions of ghrelin in the paraventricular nucleus: energy balance and neuroendocrine implications

Abstract: Ghrelin is a peptide mainly produced and secreted by the stomach. Since its discovery, the impact of ghrelin on the regulation of food intake has been the most studied function of this hormone; however, ghrelin affects a wide range of physiological systems, many of which are controlled by the hypothalamic paraventricular nucleus (PVN). Several pathways may mediate the effects of ghrelin on PVN neurons, such as direct or indirect effects mediated by circumventricular organs and/or the arcuate nucleus. The ghrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 170 publications
(291 reference statements)
0
13
1
Order By: Relevance
“…Interestingly, we found that AgRP‐Cre;Ghsr f/f mice under CR exhibited an increased fuel preference for carbohydrates, as well as a delayed switch to fatty acid metabolism after ingestion of scheduled meal in the dark phase. This contradicts the well‐accepted effect of centrally‐delivered ghrelin with respect to increasing RER and adiposity . On the other hand, the increase in RER in AgRP‐cre;Ghsr f/f mice is in line with our previous study showing that deletion of GHS‐R in all forebrain neurones ( Syn1‐cre;Ghsr f/f mice) increased RER, although it decreased body weight and percentage of fat in chow‐fed Syn1‐cre;Ghsr f/f mice .…”
Section: Discussioncontrasting
confidence: 49%
“…Interestingly, we found that AgRP‐Cre;Ghsr f/f mice under CR exhibited an increased fuel preference for carbohydrates, as well as a delayed switch to fatty acid metabolism after ingestion of scheduled meal in the dark phase. This contradicts the well‐accepted effect of centrally‐delivered ghrelin with respect to increasing RER and adiposity . On the other hand, the increase in RER in AgRP‐cre;Ghsr f/f mice is in line with our previous study showing that deletion of GHS‐R in all forebrain neurones ( Syn1‐cre;Ghsr f/f mice) increased RER, although it decreased body weight and percentage of fat in chow‐fed Syn1‐cre;Ghsr f/f mice .…”
Section: Discussioncontrasting
confidence: 49%
“…Further assessments should be done over a more detailed and careful time course. The PVN is also a critical area that integrates the ghrelin signal with various neuropsychological factors (Dos‐Santos, Reis, Perello, Ferguson, & Mecawi, 2019). However, no in vivo studies have studied neuronal activity in the PVN when combined with peripherally administered ghrelin and stress loading.…”
Section: Discussionmentioning
confidence: 99%
“…The orexigenic hormone ghrelin is secreted by gastric mucosa and pancreas, and its main site of action is the hypothalamic melanocortin system, consisting of the pro‐opiomelanocortin (POMC)‐expressing neurons, the neuropeptide Y (NPY), and agouti‐related peptide (AgRP)‐coexpressing neurons and neurons, expressing MC3R and MC4R (Kim, Leyva, & Diano, 2014). Ghrelin increases food intake and decreases fat oxidation, which chronically contribute to increased adiposity (Dos‐Santos, Reis, Perello, Ferguson, & Mecawi, 2019). In the hypothalamic arcuate nucleus of male SD rats, ghrelin activates the intracellular energy sensor AMPK in orexigenic NPY neurons, which leads to activation of these neurons (Kohno, Sone, Minokoshi, & Yada, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin increases food intake and decreases fat oxidation, which chronically contribute to increased adiposity (Dos-Santos, Reis, Perello, Ferguson, & Mecawi, 2019). In the hypothalamic arcuate nucleus of male SD rats, ghrelin activates the intracellular energy sensor AMPK in orexigenic NPY neurons, which leads to activation of these neurons (Kohno, Sone, Minokoshi, & Yada, 2008).…”
Section: F I G U R Ementioning
confidence: 99%